Revenue Administration : Autonomy in Tax Administration and the Revenue Authority Model - Crandall, William Joseph (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note focuses on the concept of autonomy and describes why it is important in public administration. There has been a tendency for governments to increase the autonomy of their departments and agencies. The basic principle is that such autonomy can lead to better performance by removing impediments to effective and efficient management while maintaining appropriate accountability and transparency. This note explains how autonomy is relevant for revenue administration and what is the range of autonomy currently practiced. The paper also describes key measures of autonomy in revenue administration.